Comparative analysis of nutrition data from national, household, and individual levels: results from a WHO-CINDI collaborative project in Canada, Finland, Poland, and Spain. Issue 1 (1st January 2003) - Serra-Majem, L; MacLean, D; Ribas, L; Brulé, D; Sekula, W; Prattala, R; Garcia-Closas, R; Yngve, A; Lalonde, M; Petrasovits, A
Abstract : Study objective: This project determined to what extent data on diet and nutrition, which were collected in a non-uniform manner, could be harmonised and pooled for international and national comparison. Design: Direct comparisons of dietary data between studies were made using food balance sheets (FBS), household budget surveys (HBS), and individual dietary data (IDS); comparisons were also made within countries. Differences in study design and methodological approaches were taken into consideration. Data from research projects from the following four World Health Organisation (WHO) Countrywide Integrated Noncommunicable Disease Intervention (CINDI) countries were included—Canada, Finland, Poland, and Spain. Main results: FBS overestimated food consumption and nutrient intake compared to IDS. Results between HBS and IDS were quite similar, except for fish, meat, pulses and vegetables, which were underestimated by HBS, and sugar and honey and cereals, which were overestimated. Percentages of energy from fat, carbohydrates and proteins were higher when estimated from FBS, HBS, and IDS respectively. Conclusions: Results suggest that estimations from these three sources of dietary data are difficult to compare because they are measuring different levels of dietary information. The understanding of their relations may be important in formulating and evaluating a nutrition policy.